The Islamic Education Service Marketing Management at KUA Penukal, Penukal Abab Lematang Ilir Regency - Salim, Amil; Berlian, Zainal; Zainuri, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to identify and analyze the steps of Islamic education service marketing management implemented by the Office of Religious Affairs (KUA) Penukal, Penukal Abab Lematang Ilir Regency. This research employs a descriptive qualitative approach with data collection through in-depth interviews, observations, and documentation. The results show that the marketing management steps include planning, organizing, implementation, and evaluation. The marketing strategy involves a community-based approach, service digitalization, and collaboration with other educational institutions. This study contributes to the literature on Islamic education management by offering a service marketing model that is relevant to the local context.